PERBANDINGAN KUALITAS SEDIAAN APUS DARAH TEPI MENGGUNAKAN AIR KERAN DAN AQUADES SEBAGAI PENGGANTI LARUTAN BUFFER - Amwalia; Eva Ayu Maharani; Dewi Astuti (JOURNAL SAINS STUDENT RESEARCH, 2026)
In the SADT staining procedure, a buffer solution with a pH range of 6.8-7.2 is used. This pH range is ideal because it is able to provide a balance between staining the cell nucleus by azure B and staining the cytoplasm by eosin Y. Buffer pH affects the quality of staining by regulating dye ionization with cell components. However, the use of standard pH buffers is sometimes limited in the laboratory, so other alternative diluents such as tap water and distilled water are used. This study aims to compare the quality of SADT staining results using pH 6.8 buffer, tap water and distilled water. This research method is quasi experiment, with posttest-only control group design based on scoring assessment of microscopic observations and significant difference test. The results of the average scoring showed a cell picture in tap water 2.50 (not good), distilled water 3.22 (good), and control 3.33 (good). Statistical tests showed no significant difference between groups with a p-value of 0.091 (p> 0.05). Conclusion: there are differences in microscopic quality based on scoring results, but statistically there is no significant difference. This shows that although there are differences in microscopic quality, blood cells can be identified.